Pelatihan Pembelajaran Teknik Dasar Renang Berbasis Rekreasi Yang Ada Di Tais Kabupaten Seluma - Dody Ertanto; Dwingki Marta Putra; Ajis Sumantri (Jurnal Dehasen Untuk Negeri, 2024)
In Seluma Regency there is a club that was founded on July 28 2023, where the club is called the SPC Swimming Club, which happened to be founded by a lecturer at Dehasen University, namely Dwingki Marta Putra. The SPC Swimming Club was founded with the aim of advancing Seluma Regency's human resources, especially in swimming sports, because in swimming sports, Seluma Regency can be said to be lagging behind other districts. This can be seen when there are swimming tournaments or championships held in both districts and cities, there are no representatives of swimming athletes from Seluma, therefore the SPC Swimming Club was established so that human resources in Seluma Regency can compete. Where the SPC Swimming Club itself has 35 students, the majority of whom are elementary school students, meaning that with the existence of the SPC Swimming Club many children are enthusiastic about taking part in the training.